Christianity and Literature: Covertly Public, Overtly Private - Marty, Martin E. (Christianity & literature, 1998)
This article is based upon an address to the Conference on Christianity and Literature at the Annual Convention of the Modern Language Association in Toronto on 29 December 1997. The invitation asked me to comment on the public/private distinction that I make as Director of the Public Religion Project and to accent the “cultural context,” which fits my History of Culture faculty assignment and three decades of writing Context, a newsletter relating religion to culture. I was to inform it theologically, which a divinity professor is supposed to be able to do, and to show some curiosity about the literary theme, as my decades-long stint as literary editor at The Christian Century should poise me to do. Under it all my limiting job description matches a badge provided me at a conference in Tübingen, where the hosts handed out identifications marked “Theologian of History,” “Theological Historian,” and “Historical Theologian.” Mine read simply, “Historical Historian.”—MEM